Tourist leisure and recreation experience at recreational forest / Mohd Jinis Abdullah - Abdullah, Mohd Jinis (2010)
Natural forest area is the backbone of forest recreation. Malaysia is a tropical country, which is endowed with tropical rain forest that is rich in diverse natural resources. These natural resources are of high tourism potential. As the only forest recreational destination in Kuala Lumpur City Centre, Bukit Nanas Recreational Forest must offer leisure and recreational opportunities to fulfill the diverse needs and requirements of the visitors. This involves establishing recreational participation and facilities usage. The study focuses on the leisure and recreational experienced of the international tourists' visiting Bukit Nanas Recreational Forest. The data was drawn from survey conducted at Bukit Nanas Recreational Forest, Kuala Lumpur. The findings from the study identify the demographic background of the visitors. Their leisure and recreation activities, travel characteristics, benefits of signages, relationships between visit behaviour and various recreational activities, motives, and attractions. Results indicated that the tourists enjoyed, satisfied, willing to make a revisit, recommend, say positive about the activities, motives, and attractions at Bukit Nanas Recreational Forest. This showed that there were significant relationship between activities, motives, attractions and visit behaviour. The assessment on tourists leisure and recreation experience will contribute to the development of an integrated recreational programme. This will benefit the nation as a whole in promoting nature based recreation within vicinity of the city.